Analysis of Efficiency and Simplification of Procedures in Sipesut Innovation (Samarinda Customs Service Information System): Building A Lean Public Service - Qisthi, Luthfilhadi; Wardiyanto, Bintoro; Setijaningrum, Erna (Journal Research of Social Science, Economics, and Management, 2025)
The Samarinda Customs Service Information System (SIPESUT) is a digital innovation developed by Samarinda Customs and Excise Office (KPPBC TMP B Samarinda) designed to simplify bureaucratic procedures and enhance service efficiency in customs administration. This study analyzes SIPESUT through the integration of various public service paradigms, including Old Public Administration (OPA), New Public Management (NPM), and Digital Era Governance (DEG), reflecting a lean, efficient, and responsive public service model. The paper begins by discussing the digital transformation in public administration and the challenges of conventional bureaucracy. It then introduces SIPESUT as an innovative response and explores its conceptual foundation within the framework of multiple public service paradigms. Using qualitative analysis and field observation data, this study highlights SIPESUT’s impact on streamlining procedures, improving efficiency, and optimizing resources, while also identifying technical, infrastructural, and human resource challenges. The findings emphasize the necessity for system integration, human resource capacity building, and infrastructure enhancement as strategic steps to support SIPESUT’s sustainability. This research contributes to the discourse on public service innovation and inspires the development of inclusive and sustainable digital public service initiatives.